Transdermal Iron Therapy in Women with Anemia: A Comparative Study of Efficacy and Tolerability Versus Oral Supplementation - Divakar, Hema; Shastri, Vijay K.; Pahan, Jayeeta (British Journal of Healthcare and Medical Research, 2025)
Background: Iron deficiency anemia (IDA) is a significant health concern among adolescent girls and women, often compounded by poor adherence to oral iron therapy due to gastrointestinal side effects. Objective: To compare the efficacy, tolerability, and compliance of two transdermal iron lotion formulations with oral iron supplementation in women with confirmed IDA. Methods: A randomized controlled trial was conducted with 300 women divided into three arms: oral iron supplementation, Transdermal Lotion 1 (iron, folic acid, B12, vitamin D), and Transdermal Lotion 2 (minimal-iron comparator). Primary outcomes included hemoglobin improvement and adherence; secondary outcomes were changes in ferritin and vitamin D levels. Results: Transdermal Lotion 1 showed higher adherence (90% vs. 65%) and fewer side effects compared to oral therapy. Hemoglobin improved >1 g/dL in 60% of the oral group and 39.8% of Lotion 1 users. Notably, 56% of Lotion 1 users improved ferritin from <30 to >50 ng/mL and 67% achieved sufficient vitamin D levels—benefits not observed with oral iron or Lotion 2. Conclusion: Transdermal iron delivery, especially Lotion 1, offers a well-tolerated, moderately effective alternative for managing anemia in women with enhanced nutritional benefits.